Description of Two New ABCB11 Mutations Responsible for Type 2 Benign Recurrent Intrahepatic Cholestasis in a French-Canadian Family - Yannick Beauséjour; Fernando Alvarez; Martin Beaulieu; Marc Bilodeau (Canadian Journal of Gastroenterology)
Benign recurrent intrahepatic cholestasis is a rare clinical entity that is caused by mutations in the canalicular transport genes. The present report describes two individuals from the same family whose symptoms were typical of the clinical characteristics of type 2 benign recurrent intrahepatic cholestasis. Sequencing of the ABCB11 gene revealed two previously unreported mutations that predict the absence of expression of the protein. The clinical presentation of the current cases are discussed, as are the differential diagnosis and genetic characteristics of the hereditary cholestatic disorders, overemphasizing the possibility of making a definite genetic diagnosis.